Arabic Learning Strategies for Early Childhood in Instagram Educational Videos: A Qualitative Content Analysis - Dini Ainun Fatma; Mega Satria Nurul Falah (Darul Yasin Al Sys, 2026)
The growing use of social media as an educational medium creates new opportunities for Arabic language learning among young children; however, limited attention has been paid to the developmental suitability of instructional strategies presented in short-form digital content. This study aimed to analyze instructional strategies for teaching mufradāt and mahārah al-kalām in the Instagram content of @abufairuzahmadridwan and interpret their compatibility with young children’s cognitive development through Jean Piaget’s constructivist perspective. Employing a qualitative content analysis design, the study purposively examined 10 Arabic learning videos through transcription, coding, categorization, data reduction, data display, and theoretical interpretation. The findings reveal two predominant instructional patterns: experiential-contextual vocabulary learning and guided contextual speaking. Vocabulary was introduced primarily through concrete objects, physical actions, demonstrations, visual representations, and familiar situations, whereas speaking activities were structured through modeling, imitation, repetition, question-and-answer exchanges, and guided oral production. From a Piagetian perspective, these strategies correspond to the preoperational stage, particularly its emphasis on concrete experience and symbolic representation, and reflect the cognitive processes of assimilation, accommodation, and equilibration. Nevertheless, opportunities for play-based learning, independent exploration, and spontaneous communication remained comparatively limited. The study concludes that short-form social media content can support developmentally appropriate Arabic language learning when linguistic input is integrated with concrete, contextual, and multimodal experiences. These findings contribute to the application of cognitive constructivism in digital early childhood language education and imply that Arabic learning content should balance guided instruction with greater opportunities for play, exploration, and child-initiated language use.